The Oxidation of Sulphide Compounds in the Order of Processing Sodium Hydrosulphides - Isma Wulansari; Wahyudi Budi Sediawan; M. Hidayat (Waste Technology, 2023)
Oxidation of spent sulfidic caustic consist of SH- ion or NaHS compound by H2O2 in neutral or acidic solution to elemental sulphur may provide a convenient and economical method for the control of sulphide wastes and their associated odors at pulp, paper and textile industry. The effects of total sulphide concentration, isothermal and nonisothermal process, catalyst loading, ratio of SH-/H2O2 and temperature on the kinetics of sulphide oxidation were investigated. Kinetic equations and activation energies of H2O2 and SH- ion to total sulphur and sulphate in aqueous solution for the non catalytic and catalytic oxidation reaction were calculated based on the experimental results. The rate of SSC oxidation was found higher at lower initial sulphide concentration and the rate of sulphide oxidation was found directly proportional to loading and hydrogen peroxide addition. Optimum total sulphide concentration was achieved when sulphide solutions were treated at pH 4 in the presence of H2O2 in the ratios SH-/H2O2 1:5.6. The potential user of H2O2 determine the optimal conditions for control of odor, corrosion and waste treatment cost due to SSC consisting of sulphur ion, sulphate ion, etc. The oxidation of sulphides into sulphates by H2O2 may be applied directly to aqueous wastes containing these odorants.